The Effect Addition Of Vitaliquid Boster With Different Doses On Feed Towards Growth And Survival Rate Of Vannamei Shrimp (Litopenaeus vannamei) With Resirculation System - Ririn Alisya Mariska; Niken Ayu Pamukas; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research aims to find out what is the optimal dose of vitaliquid boosters to increase the growth and survival of Vanname shrimp (Litopaneaus vannamei) with recirculation systems. This research was carried out for 40 days in January-February 2019 held at Laboratory of Aquaculture Technology, Faculty of Fisheries and Marine, University of Riau. The design of this research is an experimental model using Completely Randomize Design Factorial pattern (RAL) of 1 factor, 4 treatment levels and 3 replications. The treatment level of this study was P0 (feed without the addition of vitaliquid), P1 (addition of vitaliquid 5 ml / kg of feed), P2 (addition of vitaliquid 10 ml / kg of feed), P3 (addition of vitaliquid 15 ml / kg of feed). The best treatment is the treatment of (P3) additional booster doses of 15 ml / kg of feed resulting in absolute weight growth of 1,96 gr, specific growth rate of 5,61%, and survival of 91,66%. Water quality during the study was temperature ranging from 28-30 oC, pH ranged from 7.4-8, dissolved oxygen (DO) ranged from 4.2 to 4.7 mg / L, and ammonia (NH3) ranged from 0.0058-0, 0117 mg / L.kg feed. Keywords: Vitaliquid boosters, Vanname shrimp, Growth